Evolution of accretion disc reflection spectra due to a Type I X-ray burst. Issue 2 (23rd October 2021) - Speicher, J; Ballantyne, D R; Fragile, P C
ABSTRACT: Irradiation of the accretion disc causes reflection signatures in the observed X-ray spectrum, encoding important information about the disc structure and density. A Type I X-ray burst will strongly irradiate the accretion disc and alter its properties. Previous numerical simulations predicted the evolution of the accretion disc due to an X-ray burst. Here, we process time-averaged simulation data of six time intervals to track changes in the reflection spectrum from the burst onset to just past its peak. We divide the reflecting region of the disc within r ≲ 50 km into six to seven radial zones for every time interval and compute the reflection spectra for each zone. We integrate these reflection spectra to obtain a total reflection spectrum per time interval. The burst ionizes and heats the disc, which gradually weakens all emission lines. Compton scattering and bremsstrahlung rates increase in the disc during the burst rise, and the soft excess at <3 keV rises from ≈4 to ≈38 per cent of the total emission at the burst peak. A soft excess is expected to be ubiquitous in the reflection spectra of X-ray bursts. Structural disc changes such as inflation because of heating or drainage of the inner disc due to Poynting–Robertson drag affect the strength of the soft excess. Further studies on the dependence of the reflection spectrum characteristics to changes in the accretion disc during an X-ray burst may lead to probes of the disc geometry.